ANATOMI PERBANDINGAN KAYU CENDANA (SANTALUM ALBUM L.) DAN EXOCARPUS (EXOCARPUS LATIFOLIA R. Br.) - Y I Mandang (Jurnal Penelitian Hasil Hutan, 1988)
Compared   to  Santalum   album  L.,  the  wood  of  Exocarpus Latifolia R.Br. is lower  in quality.  It  is there necessary  to investigate   the  difference   of  their  wood  features   to overcome   the  unwanted   substitution or fraud possibilities.Microscopic  study  reveals that  there  are many  similarities  in wood  anatomy   between   Santalum album  L.  and Exocarpus  latifolia R. Br. They are anatomically different   only  in pore  diameter  and pore  frequency. The wood  of  Exocarpus latifolia R.Br.  has larger pore  diameter   but  lower pore  frequency. Some   differences   were  also  ob1erved  on  gross  features   of  wood.   Exocarpus latifolia   R. Br.  has  darker  sapwood color,  coarser wood  texture  and  less aromatic odour.